Dapsone‐Induced Heinz Body Hemolytic Anemia: A Case Report - Tyler Edwards; Monica Montes‐Rivera; Lucy Fu (Clinical Case Reports)
ABSTRACT Patients who develop acute anemia, without evidence of blood loss, should have a hemolysis workup including a medication review in case this could be contributing. In our patient's case, workup was significant for Heinz body hemolytic anemia due to home dapsone. Patient's anemia ultimately resolved with drug cessation.